Feelings of Disappreciation in Health Workers: Impact Analysis and Improvement Efforts - Siregar, Chivan; Pambudi, Novanda Ayu Dila Putri; Maharani, Baiq Syarifaturrayyan; Putri, Irma Santika (Jurnal Biologi Tropis, 2025)
Feelings of unappreciation among healthcare workers are a serious issue that often goes unnoticed. Contributing factors include lack of recognition from superiors and colleagues, unequal workload and compensation, and limited career development opportunities. These conditions negatively affect workers’ mental health and service quality. This study aims to identify the causes of unappreciation among healthcare workers, analyze its impact on well-being and performance, and propose strategies to enhance appreciation. A literature review was conducted using databases such as Google Scholar, PubMed, and ScienceDirect. Inclusion criteria included journal articles and books from the past ten years focusing on healthcare workers’ well-being, motivation, work environment, institutional rewards, and psychosocial aspects. Twenty-five key studies were critically reviewed. Underappreciation of healthcare workers has wide-ranging psychological, professional, and social impacts. Collaborative efforts between institutions, government, and society are essential to create a supportive environment, ensure fair recognition, and strengthen healthcare systems.